Valence Band Structure of InAs1-xBix and InSb1-xBix Alloy Semiconductors Calculated Using Valence Band Anticrossing Model - D. P. Samajdar; S. Dhar (The Scientific World Journal)
The valence band anticrossing model has been used to calculate the heavy/light hole and spin-orbit split-off energies in InAs1-xBix and InSb1-xBix alloy systems. It is found that both the heavy/light hole, and spin-orbit split E+ levels move upwards in energy with an increase in Bi content in the alloy, whereas the split E− energy for the holes shows a reverse trend. The model is also used to calculate the reduction of band gap energy with an increase in Bi mole fraction. The calculated values of band gap variation agree well with the available experimental data.